2022
DOI: 10.1007/s42979-022-01412-6
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of COVID-19 Websites of Asian Countries: An Evaluation Using Automated Tools

Abstract: Web accessibility helps in making the websites accessible for all. There has been too much research on the accessibility of websites across different domains such as education, health, banking, route services, Government portals, literature, etc. In this research, we have tried to explore the much less investigated domain of the accessibility analysis of COVID-19 vaccine registration and information websites of Asian Countries. The analysis has been done based on WCAG 2.0 and 2.1 guidelines. The evaluation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore, AChecker based on AChecker was chosen as a tool for digital website evaluation in this study. International scholars used AChecker and Access Monitor based on WCAG standards to check the accessibility of COVID19 websites in Asian countries [8], Chinese scholars used tools such as AChecker and A-prompt based on WCAG 2.0 to evaluate the accessibility of websites for the elderly [9].…”
Section: Research Statusmentioning
confidence: 99%
“…Therefore, AChecker based on AChecker was chosen as a tool for digital website evaluation in this study. International scholars used AChecker and Access Monitor based on WCAG standards to check the accessibility of COVID19 websites in Asian countries [8], Chinese scholars used tools such as AChecker and A-prompt based on WCAG 2.0 to evaluate the accessibility of websites for the elderly [9].…”
Section: Research Statusmentioning
confidence: 99%
“…Figure 9 synthesizes the manual and automatic tools used more than once in the selected articles for website accessibility evaluations (for complete information, see Table A2). (1) Achecker: The accessibility checker is a digital tool for website evaluation based on the WCAG; it is used to rapidly scan the website of interest to identify the technical accessibility errors and issues it presents [31]. (2) WAVE: this comprises a set of evaluation instruments designed to enhance the accessibility of web content for individuals with disabilities; it not only identifies numerous accessibility and WCAG errors, but it is also centered on addressing issues known to affect end users, promoting human assessment, and educating about web accessibility [16].…”
Section: Scoping Reviewmentioning
confidence: 99%
“…It is noted that of both the papers published in 2019, one [50] applies the 2.0 version but also the first version 1.0, with conformance levels A, AA, and AAA, and the other [49] applies only the 2.0 update, although the latest version was already available by that year. Furthermore, between 2019 and 2022, we found that six papers applied a combination of WCAG versions 2.0 and 2.1; studies [30][31][32][33][34]40], and all evaluated conformance levels as A, AA, and AAA.…”
Section: Rq7: What Are the Disabilities Analyzed In The Accessibility...mentioning
confidence: 99%